Breadwinning Daughters: Young Working Women in a Depression-Era City, 1929-1939 - Srigley, Katrina (Studies in gender and history, 2010)
As one of the most difficult periods of the twentieth century, the Great Depression left few Canadians untouched. Using more than eighty interviews with women who lived and worked in Toronto in the 1930s, Breadwinning Daughters examines the consequences of these years for women in their homes and workplaces, and in the city's court rooms and dance halls. In this insightful account, Katrina Srigley argues that young women were central to the labour market and family economies of Depression-era Toronto. Oral histories give voice to women from a range of cultural and economic backgrounds, and challenge readers to consider how factors such as race, gender, class, and marital status shaped women's lives and influenced their job options, family arrangements, and leisure activities. Breadwinning Daughters brings to light previously forgotten and unstudied experiences and illustrates how women found various ways to negotiate the burdens and joys of the 1930s. --Publisher's description
Keywords: 1929; 20th century; Depressions; Economic conditions; Employment History; History; Ontario Toronto; Social conditions; Toronto (Ont.); Women employees; Young women